2011
DOI: 10.1021/cm103332y
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Migration at High Temperatures in Li4Ti5O12 Studied by Neutron Diffraction

Abstract: The structure of Li 4 Ti 5 O 12 was investigated by neutron powder diffraction, and the study revealed unprecedented details about lithium migration at high temperatures. A commercial sample of the battery anode material Li 4 Ti 5 O 12 (spinel-type) was measured from room temperature to 1100 °C. Up to 500 °C, linearly increasing values for the unit cell parameter, the isotropic atomic displacement parameters, and the oxygen position are observed. At 700 °C, a change of slope occurs, which is assigned to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
47
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 36 publications
11
47
1
Order By: Relevance
“…All the atoms were fully relaxed to simulate the optimized structure of each lattice model, with a cutoff energy of 368 eV on a plane wave basis set. The calculated lattice constant for Li 4 Ti 5 O 12 was found to be 8.43 Å in this work; this value shows only a small discrepancy from the experimentally measured value of 8.35 Å, with an error of 0.96% [31]. Fig.…”
Section: Computational Detailssupporting
confidence: 43%
“…All the atoms were fully relaxed to simulate the optimized structure of each lattice model, with a cutoff energy of 368 eV on a plane wave basis set. The calculated lattice constant for Li 4 Ti 5 O 12 was found to be 8.43 Å in this work; this value shows only a small discrepancy from the experimentally measured value of 8.35 Å, with an error of 0.96% [31]. Fig.…”
Section: Computational Detailssupporting
confidence: 43%
“…The results shown in Figure 9 do not support Li at the 48f site, with the view along the c-axis in Figure S10 showing clearly an absence of residual nuclear density surrounding this site. However, a small amount of residual negative nuclear density surrounds the 32e site, indicating the possibility that this site is involved in the Li diffusion path, perhaps acting as a bridge connecting the 8a and 16c sites and lowering the energy barrier for diffusion as suggested by Laumann et al 38 The depth of density in Figure 8 represents the relative abundance of Li at each site, with the exception of the 16d site that is also occupied by Ti, where Ti also has a negative neutron-scattering length. The evolution of the density distribution on going from the charged to discharged states (during delithiation) reveals that for both anodes the Li concentration at 8a sites relatively increases, whereas the Li concentration at the 16c site decreases, showing good agreement with the calculated site occupation of Li at 8a and 16c (Figure 7).…”
mentioning
confidence: 89%
“…Then measuring the Li 4 Ti 5 O 12 over a wide temperature range (295-680 K), Vijayakumar et al demonstrated the migration of Li-ions from the tetrahedral 8a to the octahedral 16c sites and the progressive phase transition from a spinel to a defective NaCl-type structure [69]. At the high temperatures, Laumann et al identified that the Li atoms occupied split sites around the 16c positions by NPD measurement [70]. Besides, the Li-site occupation is also dependent on the lithiation process for the spinel Li 4 Ti 5 O 12 , and Aldon et al proposed that chemically inserted Li-ions were trapped in the 48f sites of the spinel structure from which they could not be extracted by electrochemical means [71].…”
Section: Li-site Occupationmentioning
confidence: 99%